Mining microbial tapestry using high-throughput sequencing and In silico analysis of Trehalose synthase (TreS) derived from hot spring metagenome - Wani, Atif Khurshid; Chopra, Chirag; Singh, Reena; Ahmad, Suhail; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP] (Elsevier, 2023)
Understanding the microbial diversity and research trends using metagenomics is important for biotechnological and environmental applications. In this study, we carried out bibliometric analysis on hot metagenomics to study the research trends. The high-throughput metagenome sequencing was used to investigate the taxonomic profile of Rajouri hot spring (RHS) located at 33.1829° N, 75.1441° with 3445 feet above the sea level. The isolated metagenomic DNA (mDNA) was subjected to sequencing using Illumina technology, and the data was processed using QIIME for taxonomic classification and diversity analysis. The results showed a high level of diversity within the microbial communities with Proteobacteria (41.03%), Actinobacteria (16.7%), and Firmicutes (7.42%) as the dominant phyla. The Shannon (3.28), Simpson (0.053), and Chao1 (198.5) indices indicate the microbial richness in RHS suggesting a more stable and resilient ecosystem. The Trehalose synthase (TreS) gene, responsible for catalyzing the conversion of maltose to trehalose, was subjected to PCR amplification, DNA sequencing, and subsequent computational analysis. Through these investigations, it was determined that the TreS protein is composed of 169 amino acids, displaying a globular conformation and possessing hydrophilic characteristics. The advancements in high-throughput sequencing technology will enable more comprehensive and accurate analysis of the hot spring metagenome, leading to a deeper understanding of the microbial communities and their interactions.
Keywords: Hot spring; Hydrolase; Metagenomics; Microbial diversity; Sequencing; Trehalose synthase